Synthesis and development of pest management modules against major insect pests of pumpkin (Cucurbita moschata) - Halder, Jaydeep; Rai, A B (The Indian Journal of Agricultural Sciences, 2020)
Field experiment was conducted in pumpkin (Cucurbita moschata Duch. ex Poir.) during summer seasons of 2018 and 2019 at Varanasi, Uttar Pradesh with a view to develop adaptable and rational pest management technology for the major insect pests of pumpkin. Among the three pest management modules, viz. biointensive module (M1), integrated module (M2) and chemical module (M3) synthesized and formulated against major insect pests of pumpkin including red pumpkin beetle (Raphidopalpa foveicollis), white fly (Bemisia tabaci) and mirid bugs (Nesidiocoris cruentatus), the integrated module (M2) comprising sprayings of DDVP 76% EC @0.75 ml/l at 20 and 30 days after sowing (DAS), Bacillus thuringiensis var. Kurstaki @ 2 g/l at 40 DAS, Imidacloprid 17.8 SL @ 0.33 ml/l at 50 DAS, Lecanicillium lecanii @5 g/l at 60 DAS and Azadirachtin 300 ppm @5 ml/l at 70 DAS was most effective in reducing the red pumpkin beetle (75 and 67.27% during 2018 and 2019, respectively), white fly (44.12 and 66.55) and mirid bug population on leaves (74.24 and 84.62) with maximum increase in the yield (291 q/ha) over chemical (287 q/ ha), biointensive modules (269 q/ha) and untreated control (208 q/ha). Considering economics of the treatments, integrated module (M2) recorded highest cost benefit ratio of 1:7.06 followed by biointensive module (1:3.41) and chemical module (1:2.77).